ROLE OF POSITRON EMISSION TOMOGRAPHY IN THE HEMODYNAMIC EVALUATION OF BRAIN TUMORS - A. A. Stanzhevskiy; A. F. Panfilenko; L. A. Tyutin; Yu. R. Ilyushchenko (Вестник рентгенологии и радиологии)
The review analyzes the literature on the use positron emission tomography (PET) with various radiopharmaceuticals in the assessment of cerebral blood flow, perfusion, the blood-brain barrier in order to investigate the biological properties, diagnosis, differential diagnosis, staging of brain neoplasms and in the evaluation of the efficiency of their treatment. The main qualitative perfusion and cerebral blood flow indicators that can be identified by PET are described in detail and compared with morphological criteria for estimation of angiogenesis and the degree of tumor tissue vascularization.